Novel spintronic effects in two-dimensional van der Waals heterostructures - Zhiyuan Zhao; Yijie Lin; Ahmet Avsar (npj 2D Materials and Applications)
Abstract Precise engineering of spin interfaces is essential for the development of spintronic devices. Two-dimensional vdW heterostructures enable atomically sharp interfaces that facilitate exploration of fundamental spin phenomena. Moreover, the discovery of two-dimensional magnetic materials has accelerated the field, leading to novel devices and spin effects. This review highlights recent advancements in vdW interfacial spin physics, innovative device structures, and emerging moiré-induced topological effects, with implications for future spintronic applications.